Influência da identificação de contatos na adesão do caso índice ao tratamento de tuberculose : estudo observacional no Estado do Paraná, Brasil, de 2008 a 2012 - Oliveira, Simoni Pimenta de (2015)
Tuberculosis (TB), infectious disease caused by Mycobacterium tuberculosis, is transmitted from person to person when an individual with the pulmonary form expels bacilli when coughing, sneezing or talking. It is expected that each new case display your contacts, people with whom lives, for examination. However, it is observed that such information is no longer made in some situations and to better understand them, was conducted observational and cross-sectional study of the SINAN data of Paraná State, Brazil. Cases of pulmonary TB in over 15 years and TB of all clinical forms in children under 15 years were included. The objective was to analyze the detection of new cases of contacts diagnosed between 2008 and 2012 and how this variable relates to membership and outcome of the treatment of the index case. Therefore, the study was divided into two phases: the first consisted of descriptive and statistical analysis of epidemiological data record and the second was conducted structured interviews with residents index cases at the 15th Regional State Health and diagnosed in 2011 and 2012. We analyzed 9867 new cases of TB in over 15 years, of which 29% did not have their contacts investigated and it was found that 61.81% of these were smear positive, demonstrating the possibility of having transmitted the disease to people who were not examined. In the group of adults who had contact record was greater adherence to treatment and the cure rate was higher. Among those younger than 15 years were found 357 cases and 21% also did not have their contacts examined. In the second phase are located only 5 of the 30 cases indexes for structured interview, mainly due to incorrect addresses. The involvement of people close, is the family arrangement, work or in other environments, is an affordable strategy, low cost and brings favorable results for the patient and contributes significantly to adherence to treatment and healing as observed in this study.